THE SOCIO-ECONOMIC CONSEQUENCES OF IMPLEMENTING DIGITAL MANAGEMENT SYSTEMS IN ENTERPRISES (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article analyzes the impact of digital technologies and information and communication technologies (ICTs) on economic development. It examines how the first and second waves of digitization contribute to expanding market coverage, increasing labor productivity, enhancing export performance, and creating new employment opportunities. Furthermore, the macroeconomic effect of the digital ecosystem development index on GDP is assessed. Empirical studies show that broadband Internet and digital platforms, such as e-commerce and B2B/B2C platforms, create new opportunities for local businesses, increase household income, and promote efficiency in the production and distribution of local digital content and services. At the same time, potential Internet disruptions and the complexity of implementing technological innovations may delay the realization of their economic impact. The article includes an analysis of the practical implementation of digitization in companies such as UZUM and Uzcard. These companies have successfully leveraged broadband Internet and digital platforms to reduce operational costs, expand sales volume, and enhance direct engagement with consumers. In this way, the article provides an academic assessment of how the digital economy positively influences both enterprise-level performance and national economic development.
Keywords: Digital technologies, information and communication technologies (ICTs), economic development, broadband Internet, export performance, UZUM, Uzcard.